Assessment of Patient Experiences in Otolaryngology Virtual Visits During the COVID-19 Pandemic. Issue 2 (June 2020) - Itamura, Kyohei; Rimell, Franklin L.; Illing, Elisa A.; Higgins, Thomas S.; Ting, Jonathan Y.; Lee, Matthew K.; Wu, Arthur W.
This study evaluates the patient experience during virtual otolaryngology clinic visits implemented during the coronavirus disease 2019 (COVID-19) pandemic. Patient satisfaction surveys were queried from January 1, 2020, to May 1, 2020, for both telehealth and in-person visits. A descriptive analysis of the question responses was performed. There were 195 virtual and 4013 in-person visits with surveys completed in this time period. Ratings related to provider-patient communication were poor for virtual visits. Telehealth has become the new norm for most health care providers in the United States. This study demonstrates some of the initial shortcomings of telehealth in an otolaryngology practice and identifies challenges with interpersonal communication that may need to be addressed as telehealth becomes increasingly prevalent.